2022
DOI: 10.3389/fdata.2022.932618
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Chronic Diseases Associated With Tooth Loss Among the US Adult Population

Abstract: BackgroundHalf of US adults aged 20–64 years have lost at least one permanent tooth; one in six adults aged 65 and over in the USA is edentulous. Tooth loss and edentulism interfere with nutritional intake and quality of life. Although selected chronic diseases (e.g., diabetes) have been identified as possible risk factors for tooth loss, data on multiple chronic diseases and on having two or more concurrent chronic diseases (multimorbidity) in relation to tooth loss are lacking. Therefore, this study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
2
10
0
1
Order By: Relevance
“…The present study confirmed that older age was associated with edentulism, as previously reported [ 8 , 20 , 21 , 36 ]. Tooth loss is considered an accurate marker of the population’s oral health and is therefore monitored in many countries.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present study confirmed that older age was associated with edentulism, as previously reported [ 8 , 20 , 21 , 36 ]. Tooth loss is considered an accurate marker of the population’s oral health and is therefore monitored in many countries.…”
Section: Discussionsupporting
confidence: 93%
“…This combination does not foretell the best outcomes for oral health, and it is likely/will likely be associated with a high edentulism experience [ 2 , 20 , 21 , 24 ]. In the present study, T2DM was a risk factor for edentulism as reported in other studies [ 8 , 9 , 21 , 34 , 36 ]. In recent years, the connection between oral health and systemic health has been widely recognized by the dental and medical professions.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations